Culture, gender and forests: social differentiation in coping and adapting to climate change and other stressors in the south west and east regions of Cameroon - Enokwena Baa, Ojongetakah (Rhodes University, Faculty of Science, Department of Environmental Science)
Climate change adaptation scholars and practitioners are beginning to acknowledge that the impact of climate change and other related shocks and stressors will be felt, and reacted to, differently across genders and other types of intersecting social categories, such as age, wealth, and culture, in rural communities. However, to date, most research unpacking these differential impacts and responses has been limited to 'men' versus 'women'. Few studies go beyond this male-female dichotomy to include the different gender structures of households and the intersection with other social factors that contribute to marginalisation, such as ethnicity. This research aimed to explore how different gendered household types in two ethnically diverse communities, the Ejagham and the Baka communities in the SSouth West and East regions of Cameroon, experienced and responded to climate change and other stressors. The central argument of the study is that social differentiation present dynamics and complexities across intersecting identities which determines varied levels of vulnerabilities, adaptive capacity, and livelihood outcomes. The study thus sets out to examine cultural and gendered differentiation in household assets and livelihood activities, how multiple shocks and stressors are experienced, and the differentiated responses to these, focussing specifically on forest and social safety nets. The findings were used to develop an integrated understanding of the complex socially differentiated dimensions of vulnerability and adaptation within the two communities and the implications for more climate secure and equitable livelihoods. The study drew on social-ecological systems, social justice, and feminist political ecology as guiding theoretical lenses. The study further integrated the Moser gender planning and Harvard analytical frameworks as tools for unpacking gender inequality. It followed a mixed methods research design that included household surveys, key informant interviews, and focus group discussions that applied participatory exercises. Financial, human, and physical capital were arguably limited within all household types in both the Ejagham and the Baka communities. Social and natural capital were the most common form of assets that households relied on, with 'savings groups' in the Ejagham communities being particularly prevalent. Most households were involved in crop cultivation and forest product collection although there were gendered and cultural differences. Collection of wild fruits, medicinal plants, and condiments, for example, was a more common livelihood activity within the Baka communities and amongst female-headed households. Cultivation of pumpkins and vegetables was dominant amongst households in Ejagham, with these being grown mainly by women, while the cultivation of yams was done by men. Across both communities, female-headed households had less ownership of land compared to male-headed households. The current pressure on agricultural land in the Ejagham communities has decreased crop productivity, with female-headed households disproportionately affected by less ownership of land and thus, options to diversify agricultural activities. Similarly, the rise in individual and private land ownership, in response to resource scarcity and large-scale deforestation in East Cameroon, has further dispossessed female-headed households in the Baka communities, already marginalised by their ethnicity, of land. Inequitable access to assets and the disparity in ownership of these assets across the study communities was both a cause and effect of households' differential livelihood activities and responses to shocks and stressors. Several of the shocks and stressors households were exposed to differed across the two sites. The Ejagham communities, being predominantly agricultural, frequently identified warming temperatures as a climatic stressor and increased sensitivity to the impacts of these. The Baka faced similar climate stressors, although more frequent storms were mentioned as a shock by a significant number of households. The impacts of these storms include damage and destruction of houses due to the traditional construction methods used. Since women are often tasked with the building of houses this adds another layer of stress for them. In terms of idiosyncratic shocks, the death of the main breadwinner was most frequently reported in both communities as a non-climatic shock, although this was higher within the Ejagham communities than in the Baka communities, and particularly so for female-headed households. The varied experiences from multiple shocks and stressors resulted in households' differential coping and adaptation responses. Among the different response options, social and forest safety nets, especially the use and sale of forest products (NTFPs) remained the main response options used by households in both communities. Forest products further supported households during periods of food shortage, especially female-headed households in the Ejagham communities. Households further supported one another through social groups such as savings, farming, hunting (particularly for men) and NTFP collection (for women) groups. By exploring social-ecological interactions, the study highlights the complexities around gender inequalities, vulnerabilities, and responses across socially differentiated groups of people which should be considered in policy, practice, and research. Several of my findings challenge mainstream discourses that generally group women, for instance, as a homogenous category when looking at vulnerability. For example, findings revealed that it is possible for different types of households, both women and men, to be both advantaged and vulnerable at the same time, depending on the shock or stressor faced and the livelihood activities they engage in. The same also applies to ethnicity.
Keywords: Climatic changes -- Cameroon; Differentiation (Sociology) -- Cameroon; Climatic changes -- Social aspects -- Cameroon; Cultural awareness -- Cameroon; Environmental justice -- Cameroon; Social justice -- Cameroon; Environmental risk assessment -- Cameroon; Political ecology -- Cameroon; Ecofeminism -- Cameroon; Social capital (Sociology) -- Cameroon; Community forests -- Cameroon; Deforestation -- Cameroon